Normalisation of airflow limitation in asthma: Post‐hoc analyses of TRIMARAN and TRIGGER. Issue 4 (17th April 2022) - Papi, Alberto; Singh, Dave; Virchow, J. Christian; Canonica, G. Walter; Vele, Andrea; Georges, George
Abstract: Background: In asthma, persistent airflow limitation (PAL) is associated with poorer control, lung function decline and exacerbations. Using post‐hoc analyses we evaluated: the relationship between post‐salbutamol PAL at screening, airflow limitation (AL) during 52 weeks treatment with extrafine beclometasone dipropionate/formoterol fumarate/glycopyrronium (BDP/FF/G) versus BDP/FF and the risk of moderate/severe asthma exacerbations. Methods: TRIMARAN and TRIGGER were double‐blind studies comparing BDP/FF/G with BDP/FF (TRIMARAN medium‐dose ICS; TRIGGER high‐dose) in adults with uncontrolled asthma. Patients were subgrouped according to post‐salbutamol PAL status at screening, and AL over the 52‐week treatment period. Results: Most patients with post‐salbutamol PAL at screening had AL at all on‐treatment visits (TRIMARAN 62.8%; TRIGGER 66.8%). A significantly higher proportion of patients had normalised airflow on ≥1 follow‐up visit when receiving BDP/FF/G than BDP/FF (TRIMARAN 44.1 vs. 33.1% [ p  = 0.003]; TRIGGER 40.1 vs. 26.0% [ p  < 0.001]). In patients with post‐salbutamol PAL at screening and normalised AL at ≥1 follow‐up visit, exacerbation rates were 15% ( p  = 0.105) and 19% ( p  = 0.039) lower in TRIMARAN and TRIGGER versus those with AL on all visits. There was a trend to lower exacerbation rates in patients receiving BDP/FF/G than BDP/FF, particularly in patients in whom AL was normalised. Conclusion: In these analyses, AL in asthma was associated with an increased exacerbation incidence. Inhaled triple therapy with extrafine BDP/FF/G was more likely to normalise airflow, and was associated with a trend to a lower exacerbation rate than BDP/FF, particularly in the subgroup of patients in whom treatment was associated with airflow normalisation. ClinicalTrials.gov: TRIMARAN, NCT02676076; TRIGGER, NCT02676089.